Factors Affecting Symptoms of Depression and Anxiety among Pregnant Women during COVID-19 Pandemic - Syauki, Aqilah Syahrina; Hartati, Hartati; Nurwany, Raissa; Aini, Syarifah (The Avicenna Medical Journal, 2024)
ABSTRACTBackground:  Mental health issues, including anxiety and sadness, are exacerbated by changes in social life. Mood and anxiety disorders, such as depression, may strike pregnant women more often than other women. In light of the current COVID-19 epidemic, this research seeks to determine what variables impact the occurrence of depressive and anxious symptoms in pregnant women.Methods:  This study made use of analytical observational research methods. In the year 2021, primary data was collected from November 1st to the 28th. To collect data, we went to seven different obstetrics clinics and handed out paper questionnaires and online surveys. This study makes use of three distinct measures: the Beck Depression Inventory (BDI), the Fear of COVID-19 Scale (FCV-19S), and the Beck Anxiety Inventory (BAI).Results:  Results showed that out of 308 pregnant women in Palembang, 13.0% had mild depression, 5.2% moderate, and 1.6% severe symptoms. Also, 41.9% of people took part in the study; among them, 31.5% experienced mild to moderate anxiety, 9.1% reported moderate to severe anxiety, and 1.3% reported severe anxiety. In the bivariate analysis, a strong correlation was found between the age of pregnant women and depressive symptoms, a significant association was found between packaging symptoms and abortion history, and a significant association was found between anxiety symptoms and fear related to COVID-19. We found statistically significant connections with all of these variables.Conclusions:  The study's results demonstrated a link between maternal age and depressive symptoms, as well as a history of abortion and anxious symptoms. The research participants also reported higher rates of anxiety and despair when they were afraid of contracting the COVID-19 virus. This highlights the critical need of mental health treatment in this context.